COMPARISON OF SCS UH AND CLARK METHODS FOR RAINFALL–RUNOFF MODEL IN DELUWANG WATERSHED: Perbandingan Metode SCS UH dan Clark UH dalam Pemodelan Hujan Aliran pada DAS Deluwang - Arifin, Muhammad; Hidayah, Entin; Widiarti, Wiwik Yunarni (Jurnal Rekayasa Sipil dan Lingkungan, 2018)
Deluwang River water source is widely used for the needs of irrigation, plantation, and the fulfillment of domestic life. Given the importance of the role of water in Deluwang watershed, then he had to do the management of watershed. The proper management of watershed hydrological modeling requires accurate. Rainfall-runoff using HEC-HMS applications. This research aims tocomparison 2 methods in direct runoff. Therefore this study uses two methods, namely SCS Unit Hydrograph method and method of Clark Unit Hydrograph. On the calibration process using daily rainfall data and daily debit year 2006, whereas in the validation process using daily rainfall data and daily debit years 2007 to 2012. The results of the calibration using Clark Unit Hydrograph method better than using SCS Unit Hydrograph method with Nash's value 0,700 than 0,539. While the results of the validation of modeling using Clark Unit Hydrograph method is better than using SCSUnit Hydrograph method with a value of Nash 0,541 than 0,368. Sungai Deluwang sumber airnya banyak dimanfaatkan untuk kebutuhan irigasi, perkebunan, serta pemenuhan kehidupan rumah tangga. Mengingat pentingnya peranan air pada DAS Deluwang, maka perlu dilakukannya pengelolaan DAS. Pengelolaan DAS yang tepat membutuhkan pemodelan hidrologi yang akurat. Pemodelan hujan aliran menggunakan aplikasi HEC-HMS. Penelitian ini bertujuan membandingkan 2 metode yang terdapat pada direct runoff. Oleh karena itu penelitian ini menggunakan dua metode, yaitu metode SCS Unit Hydrograph dan metode Clark Unit Hydrograph. Pada proses kalibrasi menggunakan data curah hujan harian dan debit harian tahun 2006, sedangkan pada proses validasi menggunakan data curah hujan harian dan debit harian tahun 2007 sampai 2012. Hasil kalibrasi menggunakan metode Clark Unit Hydrograph lebih bagus dibandingkan menggunakan metode SCS Unit Hydrograph dengan nilai Nash 0,700 berbanding 0,539. Sedangkan hasil validasi pemodelan menggunakan metode Clark Unit Hydrograph lebih bagus dibandingkan menggunakan metode SCS Unit Hydrograph dengan nilai Nash 0,541 berbanding 0,368.